Site-selective electrooxidation of methylarenes to aromatic acetals - Xiong, Peng; Zhao, Huai-Bo; Fan, Xue-Ting; Jie, Liang-Hua; Long, Hao; Xu, Pin; Liu, Zhan-Jiang; Wu, Zheng-Jian; Cheng, Jun; Xu, Hai-Chao (Nature communications, 2020)
Aldehyde is one of most synthetically versatile functional groups and can participate in numerous chemical transformations. While a variety of simple aromatic aldehydes are commercially available, those with a more complex substitution pattern are often difficult to obtain. Benzylic oxygenation of methylarenes is a highly attractive method for aldehyde synthesis as the starting materials are easy to obtain and handle. However, regioselective oxidation of functionalized methylarenes, especially those that contain heterocyclic moieties, to aromatic aldehydes remains a significant challenge. Here we show an efficient electrochemical method that achieves site-selective electrooxidation of methyl benzoheterocycles to aromatic acetals without using chemical oxidants or transition-metal catalysts. The acetals can be converted to the corresponding aldehydes through hydrolysis in one-pot or in a separate step. The synthetic utility of our method is highlighted by its application to the efficient preparation of the antihypertensive drug telmisartan. Benzylic oxygenation of methylarenes is a direct but challenging method for aldehyde synthesis from simple starting materials. Here, the authors show an electrochemical, site-selective method for the oxidation of methyl benzoheterocycles to aromatic acetals without using chemical oxidants or transition metal catalysts.